SPATIAL PATTERNS ANALYSIS OF HAZARDOUS EXOGENOUS GEOLOGICAL PROCESSES DEVELOPMENT USING GIS TOOLS WITHIN THE AREA AFFECTED BY THE FORMER KAKHOVKA RESERVOIR - Стадніченко, С.М.; Сомар, Н.П.; Лобасов, О.П.; Алексєєнкова, М.В. (Institute of Geological Sciences, NAS of Ukraine, 2025)
Military aggression against Ukraine by russia is having a catastrophic impact on the geological environment, in particular the destruction of the dam at the Kakhovka Hydroelectric Power Plant (HPP). The aim of this study was to justify approaches to the analysis and assessment of the hazardous exogenous geological processes dynamics in order to develop technologies for geological environment monitoring and support decision-making on the reconstruction of the territory and post-war economic recovery in Ukraine. The territory was ranked according to the density and frequency of occurrence of various types of processes (karst, slope processes, flooding, loess soil subsidence etc.) using statistical analysis of spatial data in the ArcGIS environment, and the area of the territory affected by these processes was determined. Analysis of the resulting map made it possible to estimate the areas in which a certain number of processes are developed: one – 47,550.0 sq. km (76.8%), two – 9,661.79 sq. km (15.6%), three – 4,374.38 sq. km (7.09%), four – 314.782 sq. km (0.5%) and five – 6,762 sq. km (0.01%). The methodology for assessing risks and forecasting the development of slope processes within the territory affected by the Kakhovka Reservoir has been improved. Based on the analysis of the conditions and factors influencing the development of hazardous geological processes using the inventory maps created, the influence of tectonics and relief was determined, and a forecasting model for the development of slope processes within the studied territory was created. An analysis of the distribution of slope processes by distance from tectonic disturbances was carried out. It was found that the areas of predicted landslide processes extend beyond the previously mapped. The results obtained will provide scientific and methodological support for estimating and assessing the damage caused to the geological environment as a result of russian armed aggression, as well as for developing remediation measures and management strategies for the affected areas. According to the principles of “Build Back Better” and “Build Back Greener,” it is necessary to take into account the problem of hazardous geological processes within the studied area by applying measures of geological environment monitoring, mapping, modeling, and forecasting as part of the development and assessment of scenarios for the economic recovery of the territory affected by the former Kakhovka Reservoir.